Detection of Apicystis bombi (Apicomplexa: Neogregarinorida) in carpenter bees of Argentina - Plischuk, Santiago (2023)
Historically, the neogregarine Apicystis bombi was isolated almost exclusively from bumble bees (Bombus spp.) where it disrupts adipose tissue, increasing hosts’ mortality rates. Records in solitary bees are scarce worldwide. To check for its presence in carpenter bees (genus Xylocopa), campaigns were performed in Argentina capturing 154 individuals of five species (X. augusti, X. splendidula, X. atamisquensis, X. frontalis, X. nigrocincta). The presence of A. bombi was detected by molecular means in X. augusti, X. atamisquensis, and X. nigrocincta in four of the nine provinces screened. The pathogenesis and eventual impact that A. bombi may cause in individuals or populations of Xylocopa species remain unknown. The presence of A. bombi in northern Argentina would be contradictory to the hypothesis that its occurrence is the exclusive result of its introduction to South America through invasive, infected exotic bumble bees.